Euphemism from a Politeness Perspective: An Exploration of the ability of Iraqi EFL learners to Use and Comprehend Euphemistic Expressions (Journal of the College of Languages (JCL), 2021)
Euphemisms are advantageous in people’s social life by turning sensitive into a more acceptable ones so that resentful feelings and embarrassment can be avoided. This study investigates the ability of Iraqi English learners in using euphemistic expressions, meanwhile, raising their awareness and the faculty members in English teaching faculties regarding the relevance of discussing the topics that demand euphemisation. This study comprised three stages: initial test, explicit instruction with activities, and a final test for the students’ development in this domain. A test has been distributed among 50 respondents, who are at the fourth year of their undergraduate study at the University of Babylon/ College of Basic Education. The low rate of producing and recognising euphemisms in the first stage of the study, it is concluded that Iraqi students that the course design in the foreign context is inadequate. After consistent training during the second stage, students have shown significant development in mastering these expressions.